Brain Tuberculoma Management Challenges: A Series of 5 Cases (Bangladesh Journal of Neurosurgery, 2019)
Although intracranial tuberculomas are not rare & account for a significant number of ICSOLs; Its clinical presentation &neuro-radiological findings sometimes lead us to a diagnostic dilemma and management challenge. Here, in this case series we are presenting diagnostic as well as management challenges we’ve faced managing patients with tuberculoma at a tertiary care hospital of Bangladesh. Intracranial tuberculomas can be situated in various locations and can mimic any lesion.Extracranial involvement is not always common, clinical presentation &neuroradiological findings sometimes not conclusive. Medical management indicated in almost all cases, as well as surgical intervention indicated in cases with neurological deficits & mass effect.Bang. J Neurosurgery 2019; 9(1): 64-68